The HSN and the Netherlands Indies: Challenge and Promise - Ulbe Bosma (Historical Life Course Studies)
In 2000 Kees Mandemakers and I started a project to trace the life courses of Dutch migrants to the Netherlands Indies. This article describes the process of data collection, the research questions and the project's main findings that have been published in various articles and a monograph. Two conclusions stand out: the first pertains to the heavily urban provenance of this migration and the second emphasizes the relatively educated and skilled background of colonial Dutch migration. This second finding contradicts earlier assumptions about the Dutch colonies as a place where undesirable elements were shovelled off. The current article further discusses findings of projects on Swiss and Luxembourger military migrations to the Netherlands Indies. An important difference between Dutch military migrants and those from other European countries regards the role of their service within a life course. While Dutch colonial military service was often the first step to make a career in colonial Indonesia, for Europeans from abroad it was rather a move of desperation as well as an attempt to earn some money that would enable them to start a business and a family in their country of birth. Their migration experience was rather a 'life cycle' migration. The article finally describes attempts to extend the HSN to the Dutch citizens born in the Netherlands Indies.